Rearing of Local Earthworms in The Mixed Media of Bagasse and Fish Waste - Darmi Buchari (Talenta Publisher, 2019)
This study aims to determine the preference of earthworms to a media, their population growth in the media, and their ability to produce vermicompost. This study was designed with a completely randomized design consisted of three (3) treatments and each treatment consisted of 7 replications. The treatments in this study were 3 species of local earthworms (Pheretima javanica, Pheretima asiatica, and Pontoscolex corethrurus). The rearing media used was the mixture of bagasse and fish waste. The parameters studied were the time needed by the earthworms to enter the media, the earthworms population growth rate, and the time needed by the earthworms in producing vermicompost. The results showed the three species tested could be lived on mixed media of bagasse and fish waste. The worm's preference to the media was determined based on the time of earthworms entering media. The fastest was Pheretima javanica (0.23 minutes), followed by Pheretima asiatica (3.09 minutes) and Pontoscolex corethrurus (6.94 minutes) (p<0.05). The population growth rate between Pheretima javanica (5.85) and Pheretima asiatica (5.71) was not significantly different, but both significantly higher than Pontoscolex corethrurus (0.29 individual/month). The time for vermicompost formation in Pheretima javanica (6 weeks) and Pheretima asiatica (6 weeks) was not significantly different, but they were significantly lower from the time for vermicompost formation in Pontoscolex corethrurus (8 weeks).